Large Magnetoelectric Coupling Near Room Temperature in Synthetic Melanostibite Mn2FeSbO6. (23rd March 2017) - Dos santos‐García, Antonio J.; Solana‐Madruga, Elena; Ritter, Clemens; Andrada‐Chacón, Adrián; Sánchez‐Benítez, Javier; Mompean, Federico J.; Garcia‐Hernandez, Mar; Sáez‐Puche, Regino; Schmidt, Rainer
Abstract: Multiferroic materials exhibit two or more ferroic orders and have potential applications as multifunctional materials in the electronics industry. A coupling of ferroelectricity and ferromagnetism is hereby particularly promising. We show that the synthetic melanostibite mineral Mn2 FeSbO6 ( R 3 ‾ space group) with ilmenite‐type structure exhibits cation off‐centering that results in alternating modulated displacements, thus allowing antiferroelectricity to occur. Massive magnetoelectric coupling (MEC) and magnetocapacitance effect of up to 4000 % was detected at a record high temperature of 260 K. The multiferroic behavior is based on the imbalance of cationic displacements caused by a magnetostrictive mechanism, which sets up an unprecedented example to pave the way for the development of highly effective MEC devices operational at or near room temperature.